Optimalisasi Pemahaman Qasidah Burdah Al-Bushiri untuk Meningkatkan Praktik Keagamaan Komunitas Kampung Malaysia Raya, Kuala Lumpur Malaysia - Choironi, Merry; Walidin, Muhammad; Masyhur, Masyhur; Bety, Bety; Anam, Faqihul; Albab, Ulil; Rahmawati, Isnaini; Sobari, Dolla; Afriani, Susi Herti; Munandar, Munandar; Oryza, Fitria; Lestari, Iffah Putri; Hidayat, Dahfa (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
his community service program focuses on optimizing the understanding of Qasidah Burdah Al-Bushiri to enhance religious practices among the community of Kampung Malaysia Raya, Kuala Lumpur, Malaysia. The program aims to deepen religious comprehension, Arabic literary literacy, and preserve Malay Islamic culture through the introduction, study, and contextual appreciation of Qasidah Burdah as a classical Islamic literary heritage. Employing participatory and spiritual-reflective approaches, the program involves direct engagement with the local women’s community to collectively read, interpret, and internalize the spiritual messages of the Qasidah Burdah. This initiative also serves as an application of Arabic language and literature knowledge beyond theory, fostering academic and cultural collaboration between Indonesia and Malaysia. The expected outcome is strengthened religious practice, cultural identity, and community solidarity amid rapid urbanization and modernization pressures in Kuala Lumpur.